Intensive care treatment in acute pulmonary embolism in Germany, 2016 to 2020: a nationwide inpatient database study - Keller, Karsten; Sagoschen, Ingo; Farmakis, Ioannis T.; Mohr, Katharina; Valerio, Luca; Wild, Johannes; Barco, Stefano; Schmidt, Frank Patrick; Gori, Tommaso; Espinola-Klein, Christine; Münzel, Thomas; Lurz, Philipp; et al. (Research and practice in thrombosis and haemostasis, 2024)
Background - Pulmonary embolism (PE) is a potentially life-threatening condition. Admission and treatment in the intensive care unit (ICU) is an important element in critically ill PE patients. - Objectives - We aimed to identify risk factors for ICU admission and differences in patient profiles regarding risk factors and comorbidities between PE patients who had to be admitted to an ICU and those who were treated in a normal ward without ICU. - Methods - We used the German nationwide inpatient sample to analyze all hospitalizations of PE patients in Germany from 2016 to 2020 stratified for ICU admission. - Results - Overall, 484,859 hospitalized PE patients were treated in German hospitals from 2016 to 2020. Among these, 92,313 (19.0%) were admitted to ICU. Patients treated in ICU were younger (69.0 [IQR, 58.0-78.0] vs 72.0 [IQR, 60.0-80.0] years; P < .001) and had higher prevalence of cardiovascular risk factors and comorbidities. In-hospital case fatality rate was elevated in PE patients treated in ICU (22.7% vs 10.7%; P < .001), and ICU admission was independently associated with increased in-hospital case fatality (odds ratio [OR], 2.54; 95% CI, 2.49-2.59; P < .001). Independent risk factors for ICU admission comprised PE with imminent or present decompensation (OR, 3.30; 95% CI, 3.25-3.35; P < .001), hemodynamic instability (OR, 4.49; 95% CI, 4.39-4.59; P < .001), arterial hypertension (OR, 1.20; 95% CI, 1.18-1.22; P < .001), diabetes mellitus (OR, 1.16; 95% CI, 1.14-1.18; P < .001), obesity (OR, 1.300; 95% CI, 1.27-1.33; P < .001), surgery (OR, 2.55; 95% CI, 2.50-2.59; P < .001), stroke (OR, 2.86; 95% CI, 2.76-2.96; P < .001), pregnancy (OR, 1.45; 95% CI, 1.21-1.74; P < .001), heart failure (OR, 1.74; 95% CI, 1.71-1.77; P < .001), atrial fibrillation/flutter (OR, 1.69; 95% CI, 1.66-1.73; P < .001), chronic obstructive pulmonary disease (OR, 1.21; 95% CI, 1.18-1.24; P < .001), and renal failure (OR, 1.92; 95% CI, 1.88-1.95; P < .001). - Conclusion - ICU treatment is an important element in the treatment of PE patients. Besides hemodynamic compromise, cardiovascular risk factors, stroke, pregnancy, and cardiopulmonary as well as renal comorbidities were independent predictors of ICU admission. Necessity of ICU admission was afflicted by increased case fatality.
Gesehen am 06.03.2025
Online verfügbar: 8. August 2024, Artikelversion: 2. September 2024